THE EFFECT OF BUSINESS RISK, FIRM SIZE, AND SALES GROWTH ON THE CAPITAL STRUCTURE OF PROPERTY AND REAL ESTATE SECTORS PERIOD OF 2018-2020 - Saphira Eka Nurfadhila; Hari Sulistiyo (Universitas Islam Lamongan, 2022)
The purpose of this study was to examine the effect of business risk, firm size, and sales growth on the capital structure of the property and real estate companies listed on the Indonesia Stock Exchange (IDX). The methodology used in this research is quantitative research with data obtained from the Indonesia Stock Exchange website (www.idx.co.id). The analytical technique used is descriptive statistics using the SPSS version 25 program. Based on the results of the study, it can be concluded that there is a significant influence between business risk and firm size with capital structure. Meanwhile, sales growth has no significant effect on capital structure. Then simultaneously or together show that business risk, firm size, and sales growth have a significant effect on capital structure.